Obtaining electrical characteristics of a PV module by FPGA based experimental system - Parlak, Koray Sener (Pergamon-Elsevier Science Ltd, 2020)
Electrical characteristics of photovoltaic (PV) modules are significant for using in PV array and standalone applications. Therefore, when designing a PV system, these characteristics must be considered. Some methods are developed to achieve the electrical characteristics of PV modules and one of them is using a capacitor where it is connected to output of the PV module as a load. This method based on measuring the current and voltage of the capacitor during its charging. Thus, the electrical characteristics of the module can be obtained by using these measurements. In this article, Field Programmable Gate Array (FPGA) based method with using a capacitor is proposed to get electrical characteristics of the PV module. The method firstly simulated in Matlab-Simulink environment and promising results are obtained. Then, the method is performed by the FPGA based experimental system. At the same time, to prove experimental results, the electrical characteristics are derived by using an electronic load device. The experimental results show that the electrical characteristics can be accurately obtained by the proposed method. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Photovoltaic modules; Electrical characteristics of; Partial shade conditions; FPGA